Standards, tariffs and trade: The rise and fall of the raisin trade between Greece and France in the late 19th century and the definition of wine - Giulia Meloni; Johan F. M. Swinnen (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2017)
There is much debate on the impact of product and process standards on trade. The conceptual arguments are complex and empirical evidence is mixed. We analyze the impact of standards and tariffs on the dramatic rise and fall of the raisin trade between France and Greece in the course of 25 years at the end of the 19th century. The case illustrates how product standards can be used to address consumer concerns and to protect producer interests. Economic conditions and French policies first stimulated Greek raisin imports. Later, changing conditions and political pressures led to the introduction of tariffs and wine standards which caused major declines in Greek exports and ultimately the bankruptcy of the Greek economy. Interestingly, this trade episode of more than a century ago still has a regulatory legacy today as it is the origin of the EU's definition of wine.
Keywords: 330; Standardisierung; Standard; Zollpolitik; Fruchthandel; Weinhandel; Wirkungsanalyse; Frankreich; Griechenland